Reward Management: A Handbook of Remuneration Strategy and Practice - Armstrong, Michael (London Kogan Page, 1998)
Based on interviews with victims, investigators, and the people who sell counterfeits, "Knockoff" reveals the link between what is perceived as "innocent fakes" and organized crime. This disturbing book will make readers squirm in their seats if they've ever purchased counterfeit goods.
Age Group: Adult
Includes bibliographical references and index.
Published in association with Hay Management.
Previous ed.: 1994.
Keywords: Compensation Management -- Great Britain -- Handbooks, Manuals, Etc